Analisis Perbandingan Harga Saham, Volume Perdagangan, Dan Frekuensi Perdagangan Saham Sebelum Dan Sesudah Pengumuman Kasus Pertama Covid-19 di Indonesia (Event Study Pada Perusahaan Telekomunikasi Yang Terdaftar di BEI) - Fanny Dewi Sukma; Aprilina Susandini (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to find out and compare the stock price, trading volume, and frequency of trading shares of telecommunication companies before and after the announcement of the first case of Covid-19 in Indonesia. The population in this study are companies that included in the Telecommunication Sub-Sector listed at IDX. The samples in this study used purposive sampling, where only 14 companies met the criteria. In this study, the data used is 30 days before and after the announcement of the first case of Covid-19 i n Indonesia. The hypothesis test used is Wilcoxon Signed Rank Test.The result showed that: 1) there is a significant differences in the stock price and trading volume of telecommunications companies before and after the announcement of the first case of Covid-19, 2) there is no significant difference in the frequency of trading shares of telecommunications companies before and after the announcement of the first case of Covid-19.